Time Discriminator for Satellite Radar Altimeter Tracker System - D. S. Borovitsky; A. E. Zhesterev; V. P Ipatov; R. M. Mamchur (Известия высших учебных заведений России: Радиоэлектроника, 2018)
The article deals with the study of quasi-optimal TOA discriminator of an onboard echo-signal tracker of the altimeter carried by a space vehicle. In modern space-based altimeters, final data processing is imposed on the ground-based center receiving information from the spacecraft through a telemetry line, while the main task of an onboard delaylocked loop is to reliably retain the received echo-signal within the tracking window. The optimum discriminator of an onboard loop providing the potential accuracy of time measurement can appear difficult to implement. In the discriminator considered an error signal is proportional to the time mismatch between the half power point of the received power pattern and the tracking window. The equation for the equivalent time fluctuation variance is derived. It is also found that the discriminator proposed is as good at tracking precision as the maximum-power-point discriminator and maximums teepness discriminator, being at the same time much more attractive in terms of hardware complexity. The theoretical results are well consistent with the computer simulation. This simulation is performed both directly and using different methods of censoring the error signal at the discriminator output to effectively neutralize possible abnormal errors that are not taken into account by theoretical analysis.